Concepts and Methods of Story telling Al-Qur'an Stories for Early Childhood: A Study of the Book of Kisah Kota-Kota Dalam al-Qur’an by Rani Yulianty - Teza, Ahmad; Sulthoni, Akhmad; Wirastho, Edy (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
The world of children is always close to the world of stories. However, it is unfortunate that today the stories that are very close to children are imaginative stories so that children are more familiar with the characters of fictional characters compared to the characters and cities that they should really know. Stories in the Qur'an should always be presented to children in a style and presentation that suits them. One of the efforts that have been made is the book Tales of Cities in the Qur'an by Rani Yulianty. This study was conducted using library research method by taking samples from 12 city stories contained in the book. This research focuses on the method of storytelling in the book and its advantages and disadvantages. This research reveals something new in the delivery of stories for early childhood, especially in terms of the story of the cities in the Qur'an. The results of this study indicate that the method of delivering the story of the Cities in the Qur'an by Rani Yulianty uses visualization, pictures, ornaments, and comic methods. The advantages of this book use light language so that it is easy to understand for children, has good visualization by displaying the location and description of the city and many interesting games for children. This book is lacking in terms of not including important lessons or taking conclusions at the end of each city story presented, the author is more likely to convey it in general on the last page of the book.